2005
DOI: 10.1007/s11183-005-0075-9
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid and Phenylalanine Ammonia-Lyase in Potato Plants Infected with the Causal Agent of Late Blight

Abstract: In tuber tissues of potato ( Solanum tuberosum L.) infected with an incompatible race of Phytophthora infestans (Mont.) de Bary, the activity of phenylalanine ammonia-lyase and the contents of free and bound salicylic acid (SA) considerably exceeded the corresponding indices in the tissues infected with a compatible race of the oomycete. The accumulation of the free form of SA apparently resulted from both enhanced SA biosynthesis and the liberation from the bound SA forms. SA accumulation in the incompatible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…These results agree with those of Mandal et al [75] who noticed that the content of endogenous salicylic acid was increased significantly in tomato plants treated with salicylic acid as a foliar spray and through root treatment under Fusarium oxysporum infection. Salicylic acid accumulation due to the pathogen or phenolic compounds application was shown to result from the enhanced activity of PAL [76]. Chen et al [77] proposed that high activity of PAL in salicylic acid -treated plants indicated that the development of acquired resistance by salicylic acid may be attributed at least partly, to the salicylic acid induced PAL gene expression and activation.…”
Section: The Data Inmentioning
confidence: 99%
“…These results agree with those of Mandal et al [75] who noticed that the content of endogenous salicylic acid was increased significantly in tomato plants treated with salicylic acid as a foliar spray and through root treatment under Fusarium oxysporum infection. Salicylic acid accumulation due to the pathogen or phenolic compounds application was shown to result from the enhanced activity of PAL [76]. Chen et al [77] proposed that high activity of PAL in salicylic acid -treated plants indicated that the development of acquired resistance by salicylic acid may be attributed at least partly, to the salicylic acid induced PAL gene expression and activation.…”
Section: The Data Inmentioning
confidence: 99%
“…There have been several reports of increased PAL activity in plants under various stresses, such as irradiation, fungal infections, and wounding (Briidenfeldt and Mohr 1988;Dubery and Franchoan 1994;Lafuente et al 2003;Panina et al 2005;Yang et al 2011;Koc and Ustun 2012). Induction of PAL gene expression or increasing its enzyme activity by stress-related hormones and herbicides has been extensively reported (Jiang and Joyce 2003;Lee et al 2003;Panina et al 2005;Sakurai et al 2007;Ferrer et al 2008;Moura et al 2010;Jayalakshmi et al 2011;Jeong et al 2012;Koc and Ustun 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of PAL gene expression or increasing its enzyme activity by stress-related hormones and herbicides has been extensively reported (Jiang and Joyce 2003;Lee et al 2003;Panina et al 2005;Sakurai et al 2007;Ferrer et al 2008;Moura et al 2010;Jayalakshmi et al 2011;Jeong et al 2012;Koc and Ustun 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The elevations in PAL activity has been shown in both compatible and incompatible plant interactions with environmental cues. However, the increase in this enzyme activity and accumulation of its mRNA have been found to be more rapid and higher in the cases of incompatible interactions (Liang et al, 1989;Panina et al, 2005;Choudhary, 2011). The previous reports have shown that the activity of PAL in response to phytophthora capsici attack can be elevated up to about 80% in pepper during nine days (Hu-zhe et al, 2005).…”
Section: Changes In Enzyme Activitiesmentioning
confidence: 99%